Remineralizing Agents in the Prevention of Caries: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Divya Bhavani Vasamsetti; Srinivas Pachava; Devaki Talluri (Wolters Kluwer Medknow Publications, 2021)
Introduction: The systematic review presented here aims to determine and find out the clinical efficacy of various remineralization agents for early enamel caries. Materials and methods: An aggregate of 240 articles has been retrieved from PubMed, Cochrane Library, Trip, and Google scholarly databases from 2010 to 2020, of which 18 randomized controlled trials (RCTs) have been integrated into this systematic review, and six of which were considered for meta-analysis. The risk of bias in each study was evaluated using the Cochrane collaboration's tool. Results: Ten of the 18 studies suggest that carious lesions are successfully minimized by remineralization. Four studies showed superior efficacy of casein phosphopeptide and amorphous calcium phosphate (CPP-ACP) in the remineralization of white spot lesions. There was no statistically significant difference (standard mean difference = −0.18, 95% confidence interval: −0.48 to 0.12, P = 0.23) between the experimental and control groups. Conclusion: This review has demonstrated an absence of dependable proof supporting the clinical adequacy of remineralizing agents. Therefore, RCTs in well-designed forms are needed to enhance all sorts of evidence in this field.